Biportal endoscopic lumbosacral foraminotomy in dogs: technical feasibility and anatomical assessment in cadavers - Kim, Jiyoon; Lee, Haebeom; Jeong, Jaemin; Jeon, YoungJin (Frontiers in Veterinary Science, 2025)
IntroductionLumbosacral foraminal stenosis (LSFS) in dogs, a subtype of degenerative lumbosacral disease, leads to nerve root compression and clinical signs such as pain or pelvic limb dysfunction. Traditional decompression techniques—such as dorsal laminectomy or lateral foraminotomy—have limitations, including restricted access, tissue disruption, and prolonged recovery. To address these challenges, this study evaluated the technical feasibility and safety of biportal endoscopic lumbosacral foraminotomy (BELF), a minimally invasive technique adapted from human unilateral biportal endoscopy (UBE), for decompressing the lumbosacral foramina in canine cadavers.MethodsBELF was performed bilaterally on nine canine cadavers (18 foramina) after initial refinement in a pilot study using three cadavers. Key outcome measures included computed tomography (CT)-based measurements of foraminal area at the entry, middle, and exit zones pre-and postoperatively, intraoperative endoscopic video evaluation of anatomical visualization and surgical performance, and a feasibility scoring system (ratings: Excellent, Good, Fair, Poor).ResultsBELF was successfully completed in all specimens without causing damage to normal anatomical structures or requiring conversion to open surgery. The mean operative time was 42.17 ± 13.27 min. Postoperative CT showed significant foraminal enlargement at all level; entry (+53.8%), middle (+81.6%), and exit (+119.8%) compared to preoperative measurements (all p < 0.001). Critical anatomical structures were preserved with clear endoscopic visualization, and all procedures were rated as Excellent or Good on the feasibility scale.ConclusionBELF enabled effective and minimally invasive decompression of the lumbosacral foramina with no observed damage to critical anatomical structures. These results support the feasibility of BELF and its potential clinical utility in managing LSFS in dogs.